Gaya Hidup Remaja Shopaholic dalam Trend Belanja Online di Shopee - Else Brilianaza; Arief Sudrajat (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2022)
This study aims to describe the lifestyle of shopaholic teenagers in online shopping trends at shopee. Developments in the field of technology have changed people's lifestyles to become more practical. Today's society is more likely to do online shopping activities because it is considered very efficient and effective. This study uses a literature study research method whose data is obtained from several previous studies and other sources such as articles, journals, books and documents related to the theme of this research. This study shows that shopee is the world's leading online shopping application that sells a variety of needs that can be easily accessed via smartphones. However, without realizing it, online shopping activities actually foster a shopaholic nature for some people, especially teenagers. Teenagers today shop not according to need, but for sheer pleasure. Because teenagers pay more attention to symbols related to consumption which are used as identities, social and cultural strata.